Understanding the pros and cons of spine surgery for ankylosing spondylitis: experience from a single institution study - Mohammadreza Chehrassan; Mohammadreza Shakeri; Farshad Nikouei; Saeed Sabbaghan; Behnam Sour; Ebrahim Ameri Mahabadi; Hasan Ghandhari (BMC Rheumatology)
Abstract Introduction Ankylosing Spondylitis (AS) presents a complex inflammatory condition with significant impact on patients’ lives. Despite advancements in understanding its pathogenesis, comprehensive elucidation remains elusive. This study investigates the outcomes of corrective spine surgery in AS patients, aiming to optimize management strategies. Methods A retrospective cohort study was conducted, including 28 AS patients undergoing corrective surgery from 2016 to 2021. Surgical procedures primarily targeted realignment of the spine to alleviate deformities. Results Radiological evaluations pre- and post-operatively revealed substantial improvements in sagittal balance and kyphosis correction. The mean correction of local kyphosis at the osteotomy site was 30.9 degrees. Minor surgical complications, though present, were managed effectively. Conclusion While acknowledging surgical complexities and potential complications, meticulous patient selection and appropriate techniques mitigate risks. This study emphasizes the pivotal role of surgical intervention in improving quality of life, particularly by addressing sagittal vertical axis and forward gaze disorders.